2013
DOI: 10.1097/dcr.0b013e318289366e
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Outcomes of Robot-assisted Laparoscopic Rectopexy for Rectal Prolapse

Abstract: Long-term results of robot-assisted laparoscopic rectopexy are satisfying. Further studies comparing robot-assisted and conventional laparoscopy, including cost-effectiveness, are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 16 publications
2
25
1
1
Order By: Relevance
“…Laparoscopic ventral mesh rectopexy (LVMR) is emerging as the treatment of choice for rectal prolapse in Europe [3]. More recently, ventral mesh rectopexy has been performed using a robotic approach with evidence supporting feasibility, safety and good functional outcomes [3][4][5][6][7][8][9][10][11][12][13][14][15][16]. A robotic approach is a particularly useful technique in the restricted space of the pelvis due to enhanced visibility from greater field magnification and three-dimensional imaging, as well as improved dexterity from the use of multiarticulated instruments, elimination of physiologic tremor and an improved eye-hand-target axis [17,18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Laparoscopic ventral mesh rectopexy (LVMR) is emerging as the treatment of choice for rectal prolapse in Europe [3]. More recently, ventral mesh rectopexy has been performed using a robotic approach with evidence supporting feasibility, safety and good functional outcomes [3][4][5][6][7][8][9][10][11][12][13][14][15][16]. A robotic approach is a particularly useful technique in the restricted space of the pelvis due to enhanced visibility from greater field magnification and three-dimensional imaging, as well as improved dexterity from the use of multiarticulated instruments, elimination of physiologic tremor and an improved eye-hand-target axis [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there is evidence to suggest that compared to laparoscopic surgery, robotic surgery may provide ergonomic benefits for the surgeon [19,20]. Most reports of robotic ventral mesh rectopexy (RVMR) come from singleinstitution reviews in Europe and typically include a combined analysis of RVMR along with other types of laparoscopic and/or robotic surgery for rectal prolapse [4][5][6][7][8][9][10][11][12][13][14]. To our knowledge, this report is the first to focus on outcomes of RVMR for rectal prolapse in the USA.…”
Section: Introductionmentioning
confidence: 99%
“…Robotic dissections for benign rectal disease, rectal prolapse and inflammatory bowel disease, however, are not as well described [7, 8]. …”
Section: Introductionmentioning
confidence: 99%
“…Since then several other case series using a variety of techniques have been described. [50][51][52] Outcomes in these studies showed low recurrence rates and good functional outcomes. A recent meta-analysis comparing laparoscopic to robotic ventral mesh rectopexy found that robotic rectopexy had similar functional outcomes and conversion rates compared with laparoscopy but longer operative times with increased costs.…”
Section: Robotic Rectopexymentioning
confidence: 99%